Structured Perceptions During Prolonged Sedation in a Patient with Advanced HIV and Severe COVID-19: A Case Report and Analysis of Possible Clinical-Phenomenological Correlations - Altunian, Rita de Cássia Silva Gonçalves; Ferraz de Oliveira, Ana Paula; Gonçalves, Washington Luiz Silva (Brazilian Journal of Case Reports, 2026)
Subjective experiences occurring during prolonged sedation in critically ill patients remain poorly understood and are often attributed to delirium and retrospective memory reconstruction. We report the case of a 53-year-old male healthcare professional and university lecturer with advanced HIV infection, severe COVID-19, pneumocystosis, and pulmonary histoplasmosis, who developed severe acute respiratory distress syndrome requiring invasive mechanical ventilation, moderate-to-deep sedation, neuromuscular blockade, and tracheostomy. Following clinical recovery and gradual withdrawal of sedation, the patient described structured perceptual experiences involving sensations of drowning, confinement, environmental vapors, food perception, and recognition of a family member’s voice. Some of these experiences showed plausible temporal correspondence with events documented in the medical record, including ventilatory support, inhalation therapies, dietary changes, and transient episodes of altered sedation levels during family visits. The discussion considers alternative mechanisms, including delirium, hypoxia, COVID-19-associated neuroinflammation, HIV-related neurocognitive vulnerability, and potential effects of the pharmacological agents used during hospitalization. This case does not allow causal inferences or confirmation of specific perceptual processing mechanisms during sedation; however, it suggests that complex subjective experiences may occur during critical illness and deserve further investigation, particularly in the context of humanized intensive care practices.